WHEN MOTIVATION DOESN’T PREDICT ACADEMIC PERFORMANCE: A CROSS-SECTIONAL STUDY AMONG MEDICAL STUDENTS - Madani, Muhammad Tazkia; Akil, Syafarinah Nur Hidayah; Yuliyanasari, Nurma; Utama, Reza (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Learning motivation is one of the internal psychological factors that influence student academic achievement. The strength and consistency of this relationship remain under debate. However, it encourages the importance of research to determine the role of motivation in academic achievement.Aims: This study aims to determine the relationship between learning motivation and MCQ block exam results in undergraduate medical students.Methods: This research is an observational analytic quantitative study with a cross sectional approach. The study population was second to fourth year preclinical students. Sampling with proportionate stratified random sampling obtained 196 students. Learning motivation was assessed using a validated instrument, the MSLQ, and academic performance was measured by the students’ latest block MCQ examination score. Spearman correlation tests were performed on the relationship. Results: The highest average learning motivation is found in the extrinsic dimension (94.9%), followed by the dimensions of task values and learning of belief (94.4%), intrinsic dimensions (84.7%), and self-efficacy (84.2%). Highly motivated students scored lower (66.9%) than moderately motivated students who scored lower (76.2%). However, the analytic revealed no statistically significant correlation between learning motivation and academic performance (p>0,05). Conclusion: Even though there were high importance of motivation in learning, this study found no significant correlation between learning motivation and academic performance.